If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13T + -40 = 9T Reorder the terms: -40 + 13T = 9T Solving -40 + 13T = 9T Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '-9T' to each side of the equation. -40 + 13T + -9T = 9T + -9T Combine like terms: 13T + -9T = 4T -40 + 4T = 9T + -9T Combine like terms: 9T + -9T = 0 -40 + 4T = 0 Add '40' to each side of the equation. -40 + 40 + 4T = 0 + 40 Combine like terms: -40 + 40 = 0 0 + 4T = 0 + 40 4T = 0 + 40 Combine like terms: 0 + 40 = 40 4T = 40 Divide each side by '4'. T = 10 Simplifying T = 10
| (-1+3)7=14 | | m^2-12m=-27 | | 17p+8=110 | | -4/7-1/9= | | 5U-50=U+22 | | 3B-15=B+23 | | X^4-7x^3+3x^2+31x+20=0 | | -x(14-3x)=12 | | X^3+4x^2+5=0 | | 16x^2+x+385= | | -x^3-9x=0 | | g*4=25-(3*4) | | -3x+5y=-7.5 | | g*4=25-(3)(4) | | 3x^2=10+13x | | -6+4=x+8 | | 18=10-2m | | -7-2x=9 | | 4x^2-12=2x | | 3(x-3)=-7x+51 | | 100+40=x | | 0=10x-7+10x | | 3-10x-8x(x)=0 | | x-(-18)=-20 | | 1800=6x | | 7-6x=12-4x-2x | | 4(m-10)=-2m+14 | | 6x-6y=7 | | y-5x-12x=-1 | | 2700=9x | | X+30=27 | | 6(z+3)-20= |